Apakah Kondisi Keuangan Rumah Sakit di Indonesia Sehat? (Evaluasi Kinerja Keuangan Pra, Era, dan Pasca Pandemi Dengan Financial Discriminant Models) - Wiguna, I Gd Nandra Hary; Dewi, Nyoman Ayu Wulan Trisna; Julianto, I Putu (Universitas Pendidikan Ganesha, 2024)
The importance of the public knowing the financial condition of hospitals is to know the availability of health services, financial transparency, improve hospital performance, and participate in decision making. Currently, the health industry in Indonesia is being hit by a crisis of public confidence after the pandemic. The reason is, people are starting to prefer treatment abroad rather than in Indonesia. This type of research is descriptive comparative which aims to determine the financial health conditions of hospitals in Indonesia before, during and after the pandemic. The research was conducted at hospitals listed on the Indonesia Stock Exchange from 2019 to 2022. Research data analysis was carried out using financial discriminant models. This research focuses on analyzing financial conditions using the Springate and Zmijewski model. The research results show that with the springate model in 2019 the SRAJ company experienced an unhealthy financial condition. Meanwhile, with the Zmijewski model, all hospitals have a healthy financial condition. There were no significant differences in financial conditions in the time period studied.